Yellow passion fruit reaction to Xanthomonas axonopodis pv. passiflorae and to Cowpea aphid-borne mosaic virus - Costa, Anne Pinheiro (2018)
Yellow passion fruit (Passiflora edulis Sims) yield and longevity have been drastically reduced by bacterial spot (Xanthomonas axonopodis pv. passiflorae - Xap) and passion fruit woodiness disease (PWD) (Cowpea aphid-borne mosaic virus - CABMV). This study was aimed at evaluating the reaction of 11 genotypes of yellow passion fruit, based on the reaction of their progenies, to both mechanically inoculated Xap and CABMV, under greenhouse conditions. There was a progressive increase in bacterial spot and PWD severity with time. BRS Gigante Amarelo, MAR20#12, and MAR20#34 were selected as the progenies with lowest bacterial spot severity and disease progress over time. MAR20#2005, EC-L-7, UnB2015-1, and EC-3-0 presented the lowest PWD severity and disease progress over time. These progenies, along with individual plants from other progenies in which disease severity was significantly low until the last evaluation, will be cloned and tested again for Xap and CABMV, including other isolates.